2022
DOI: 10.3390/pharmaceutics15010020
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive 3D-Printed Skin Drug Delivery Polymeric Films: From the Drug Loading in Mesoporous Silica to the Manufacturing Process

Abstract: The alliance between 3D printing and nanomaterials brings versatile properties to pharmaceuticals, but few studies have explored this approach in the development of skin delivery formulations. In this study, clobetasol propionate (CP) was loaded (about 25% w/w) in mesoporous silica nanomaterial (MSN) to formulate novel bioadhesive and hydrophilic skin delivery films composed of pectin (5% w/v) and carboxymethylcellulose (5% w/v) by 3D printing. As a hydrophobic model drug, CP was encapsulated in MSN at a 3:1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…This hypothesis was supported by comparing the magMCM-CQ curve with its respective physical mixture (magMCM mixed with crystalline CQ), in which a signal of the CQ melting point can be seen, although with less intensity due to the small CQ content in the total sample. The amorphization process has been reported for silica-based mesoporous materials [ 47 , 48 ] and was attributed to the confinement effect of the drug by the pore walls [ 21 ]; small and dispersed quantities of the drug could have their crystallization capacity hampered, thereby increasing drug solubility [ 19 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was supported by comparing the magMCM-CQ curve with its respective physical mixture (magMCM mixed with crystalline CQ), in which a signal of the CQ melting point can be seen, although with less intensity due to the small CQ content in the total sample. The amorphization process has been reported for silica-based mesoporous materials [ 47 , 48 ] and was attributed to the confinement effect of the drug by the pore walls [ 21 ]; small and dispersed quantities of the drug could have their crystallization capacity hampered, thereby increasing drug solubility [ 19 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement is due to the prevalence of the drug’s amorphous form when encapsulated, which increases the drug dissolution/release rate and bioavailability. This feature is provided by the pore confinement effect, which can be achieved using MCM-41 as a nanocarrier [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A complete diffusion of IVM from an ethanolic solution (96 ± 2%) occurred after 48 h along with a similar release profile observed for the IVM-MCM (78 ± 3%). By contrast, crystalline IVM dispersed in an aqueous medium had very limited diffusion through the dialysis bag (35 ± 7%), most likely due to its low solubility in the aqueous medium and, consequently, low dissolution rate, as previously discussed for other poorly water-soluble drugs [ 38 ]. These results indicate an improvement in the apparent aqueous solubility of IVM when nanoencapsulated in the pores of MCM-41.…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed a release profile identical to that of the drug in solution, providing evidence for the enhanced aqueous solubility of triamcinolone [ 37 ]. Similarly, the incorporation of clobetasol propionate in MCM-41 silica induced an alteration from a crystalline to an amorphous state, facilitating the drug dissolution process and subsequently increasing its apparent solubility [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation